2012
DOI: 10.1175/jtech-d-11-00184.1
|View full text |Cite
|
Sign up to set email alerts
|

Averaging-Related Biases in Monthly Latent Heat Fluxes

Abstract: Seasonal-to-multidecadal applications that require ocean surface energy fluxes often require accuracies of surface turbulent fluxes to be 5 W m 22 or better. While there is little doubt that uncertainties in the flux algorithms and input data can cause considerable errors, the impact of temporal averaging has been more controversial. The biases resulting from using monthly averaged winds, temperatures, and humidities in the bulk aerodynamic formula (i.e., the so-called classical method) to estimate the monthly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
1
15
2
Order By: Relevance
“…The difference in the mixed-layer depth computed by the KPP scheme is very similar to what is shown in Figure 1 for the AML experiments. This is not consistent with previous studies (Gulev, 1994(Gulev, , 1997Hughes et al, 2012), where the lack of high-frequency wind variance is expected to significantly reduce the magnitude of turbulent air-sea fluxes. In fact, because the atmospheric temperature is prescribed in this experiment, the ocean-atmosphere temperature differences increase, as shown in Figure 3 (bottom right panel) for the subtropical gyre.…”
Section: A Prescribed Atmospherecontrasting
confidence: 99%
See 1 more Smart Citation
“…The difference in the mixed-layer depth computed by the KPP scheme is very similar to what is shown in Figure 1 for the AML experiments. This is not consistent with previous studies (Gulev, 1994(Gulev, , 1997Hughes et al, 2012), where the lack of high-frequency wind variance is expected to significantly reduce the magnitude of turbulent air-sea fluxes. In fact, because the atmospheric temperature is prescribed in this experiment, the ocean-atmosphere temperature differences increase, as shown in Figure 3 (bottom right panel) for the subtropical gyre.…”
Section: A Prescribed Atmospherecontrasting
confidence: 99%
“…This question arises from the recognized contribution of the fast-varying winds associated with synoptic weather systems to maintain realistic turbulent air-sea fluxes (Gulev, 1994;Hughes et al, 2012;Jung et al, 2014;Ponte & Rosen, 2004;Wu et al, 2016;Zhai et al, 2012) and upper-ocean vertical mixing (Condron & Renfrew, 2013;Holdsworth & Myers, 2015;Wu et al, 2016). This question arises from the recognized contribution of the fast-varying winds associated with synoptic weather systems to maintain realistic turbulent air-sea fluxes (Gulev, 1994;Hughes et al, 2012;Jung et al, 2014;Ponte & Rosen, 2004;Wu et al, 2016;Zhai et al, 2012) and upper-ocean vertical mixing (Condron & Renfrew, 2013;Holdsworth & Myers, 2015;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the annual mean and seasonal cycle of the various components of the stress and buoyancy flux in the CORE normal year forcing products are reasonably well documented (Griffies et al, ; Large and Yeager, ), and the global patterns are, to a first approximation, consistent with other estimates, although there are significant outstanding uncertainties and differences, for example, in high‐latitude buoyancy fluxes (Bourassa et al, ; Cerovečki et al, ). In addition, subseasonal wind variability has a significant rectified impact on the mean and seasonal cycle of the air‐sea fluxes (e.g., Gulev, ; Hughes et al, ; Lin et al, ; Ponte and Rosen, ). Hence, it is important that this forcing product includes a climatological representation of temporal variability on periods ranging from 1 year to 12 hr (i.e., 6‐hr resolution), and therefore, it includes the majority of the subseasonal atmospheric variance of interest to this study, including 2‐ to 10‐day synoptic variability (wind speed power spectra are shown in the Figure S8).…”
Section: Model Setup Rationale and Metricsmentioning
confidence: 99%
“…Important cases of undersampling also occur when observations are made conditionally, for example, only in clear or nonprecipitating conditions. Undersampling can result in large and non-Gaussian errors (Gulev et al 2007a,b) and spatial/temporal inhomogeneity in error characteristics (Schlax et al 2001;Hughes et al 2012). Furthermore, scales smaller than the scale of the observation network can alias onto the larger scales that are resolved.…”
Section: Momentum (Wind Stress)mentioning
confidence: 99%